2008
DOI: 10.1177/1367493508096204
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized children drawing their pain: the contents and cognitive and emotional characteristics of pain drawings

Abstract: Describing pain is difficult. Children like to draw, and through their drawing they reveal worrying issues. This study aimed to examine how hospitalized children express pain through drawings, and was carried out by examining children's thematic drawings of pain. A comparison was made between hospitalized children and healthy control groups with respect to the thematic contents and cognitive and emotional characteristics of pain drawings. The drawings were sorted in categories on the basis of content, and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 36 publications
1
48
0
8
Order By: Relevance
“…The disciplinary background of the first authors varied and included art therapists (n ¼ 2) (Lyshak-Stelzer, Singer, St. John, & Chemtob, 2007;Martin, 2008); nurses (n ¼ 3) (Brewer, Gleditsch, Syblik, Tietjens, & Vacik, 2006;Madden, Mowry, Gao, McGuire Cullen, & Foreman, 2010;Rollins, 2005); psychotherapists (n ¼ 2) (Epp, 2008;Wallace et al, 2004); psychologists (n ¼ 2) (Favara-Scacco, Smirne, Schilirò, & Di Cataldo, 2001;Stefanatou, 2008); counsellors (n ¼ 1) (Beebe, Gelfand, & Bender, 2010); music therapists (n ¼ 1) (Colwell, Davis, & Schroeder, 2005); learning and research services from the department of pediatrics (n ¼ 1) (Kortesluoma, Punamäki, & Nikkonen, 2008); interior designers (n ¼ 1) (Eisen, Ulrich, Shepley, Varni, & Sherman, 2008); social workers (n ¼ 1) (Hamama & Ronen, 2009), anthroposophic medical doctors (n ¼ 1) (Hamre et al, 2009); and population health providers (n ¼ 1) (Mueller, Alie, Jonas, Brown, & Sherr, 2011). Overlap between disciplinary backgrounds of first authors was noted, predominantly within disciplines of art therapy and psychology (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disciplinary background of the first authors varied and included art therapists (n ¼ 2) (Lyshak-Stelzer, Singer, St. John, & Chemtob, 2007;Martin, 2008); nurses (n ¼ 3) (Brewer, Gleditsch, Syblik, Tietjens, & Vacik, 2006;Madden, Mowry, Gao, McGuire Cullen, & Foreman, 2010;Rollins, 2005); psychotherapists (n ¼ 2) (Epp, 2008;Wallace et al, 2004); psychologists (n ¼ 2) (Favara-Scacco, Smirne, Schilirò, & Di Cataldo, 2001;Stefanatou, 2008); counsellors (n ¼ 1) (Beebe, Gelfand, & Bender, 2010); music therapists (n ¼ 1) (Colwell, Davis, & Schroeder, 2005); learning and research services from the department of pediatrics (n ¼ 1) (Kortesluoma, Punamäki, & Nikkonen, 2008); interior designers (n ¼ 1) (Eisen, Ulrich, Shepley, Varni, & Sherman, 2008); social workers (n ¼ 1) (Hamama & Ronen, 2009), anthroposophic medical doctors (n ¼ 1) (Hamre et al, 2009); and population health providers (n ¼ 1) (Mueller, Alie, Jonas, Brown, & Sherr, 2011). Overlap between disciplinary backgrounds of first authors was noted, predominantly within disciplines of art therapy and psychology (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the 16 studies took place in hospital environments (Brewer et al, 2006;Colwell et al, 2005;Eisen et al, 2008;Favara-Scacco et al, 2001;Hamre et al, 2009;Kortesluoma et al, 2008;Lyshak-Stelzer et al, 2007;Madden et al, 2010;Rollins, 2005;Stefanatou, 2008;Wallace et al, 2004). Of these, the majority (n ¼ 8) occurred in inpatient settings (Brewer et al, 2006;Colwell et al, 2005;Eisen et al, 2008;FavaraScacco et al, 2001;Kortesluoma et al, 2008;Lyshak-Stelzer et al, 2007;Rollins, 2005;Stefanatou, 2008).…”
Section: Context Of Arts-based Interventionmentioning
confidence: 94%
“…For example, research on asthma among inner-city school-aged children and their families used drawings, along with explanatory models, to explore beliefs about asthma [48]. Illustrations, along with interviews, were also used to explore experiences of childhood chronic illness [46], stressors of children with cancer [49], hospitalization of children with pervasive developmental disorder [50], and pain [51]. Sartain and colleagues used illustrations to explore childhood chronic illness and found that children were competent interpreters of their world [46].…”
Section: Research With Childrenmentioning
confidence: 99%
“…Although there are publications concerning the quality of life of children in pain under palliative care and their families, there is a scarcity of studies that analyze the experience from the perspective of children and adolescents under palliative care regarding the management of pain in their daily lives (13)(14)(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the increase in the frequency of chronic diseases in all age groups, it is necessary for nurses and other health professionals to understand through their own accounts the experiences of children and adolescents who are suffering from pain and are receiving palliative care, making it possible to act adequately in the evaluation, management and relief of pain (10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%